2018
DOI: 10.1007/s00330-018-5672-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement alters ascending aortic blood flow and wall shear stress patterns: A 4D flow MRI comparison with age-matched, elderly controls

Abstract: Background With the implementation of transcatheter aortic valve replacement (TAVR) in lower-risk patients, evaluation of blood flow characteristics and the effect of TAVR on aortic dilatation becomes of considerable interest. We employed 4D flow MRI in the ascending aorta of patients after TAVR to assess wall shear stress (WSS) and compare blood flow patterns with surgical aortic valve replacement (SAVR) and age-and gender-matched controls. Methods Fourteen post-TAVR patients and ten age-and gender-matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…All ARR studies reported data on the flow pattern or helicity in the aortic arch, with four also reporting WSS, and four reporting PV values. Three studies of isolated AVR identified by the initial search criteria did not provide characteristics of the native valve type of included patients ( 60 62 ). These were therefore not included in the summary table, however their results were deemed to be important in understanding post-operative hemodynamic changes, and have been reviewed below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All ARR studies reported data on the flow pattern or helicity in the aortic arch, with four also reporting WSS, and four reporting PV values. Three studies of isolated AVR identified by the initial search criteria did not provide characteristics of the native valve type of included patients ( 60 62 ). These were therefore not included in the summary table, however their results were deemed to be important in understanding post-operative hemodynamic changes, and have been reviewed below.…”
Section: Resultsmentioning
confidence: 99%
“…To date few studies have examined the hemodynamic effects after TAVI, and none have included BAV patients. One report found TAVI results in increased flow eccentricity and flow displacement in the AAo compared to surgical AVR and controls ( 62 ). Others have shown reduced helical flow with TAVI (Edwards Sapien XT) compared to bioprosthetic AVR, but still abnormal compared to healthy controls ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…All datasets [ 5 ] as well as a subgroup of patients with repaired coarctation and healthy subjects [ 29 ] were previously used for the evaluation of abnormal magnitude of hemodynamics. Furthermore, a subgroup of the healthy subjects was used to evaluate abnormal hemodynamics in patients with transcatheter aortic valve repair and implantation of a bileaflet mechanical valve [ 30 , 31 ]. All participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The work by Bolleche and others demonstrates that WSS is now a reliable technique, capable of being deployed in a routine clinical setting (1,10,11). What is now needed are large, prospective longitudinal studies that link these observations to clinically relevant outcomes.…”
Section: Editorialmentioning
confidence: 99%